Integrating Artificial Intelligence into Indonesia’s Defense Policy for Strategic Decision-Making - Yusman, Faisal; Kartiningsih, Yuli; Djansena, Alradix; Supriyadi, Asep Adang (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2025)
The transformation of Indonesia's national defense policy in the digital era requires the integration of Artificial Intelligence as a strategic instrument to enhance analytical and decision-making capabilities. This study aims to formulate an AI-based defense policy framework that is responsive to the dynamics of modern threats, as well as to identify the challenges and opportunities in its implementation. The research method used is a qualitative approach through document study and policy analysis that includes national regulations, academic literature, and global practices. The results of the study indicate that Indonesia still faces a number of fundamental obstacles, such as the absence of a national ethics framework for military AI, low institutional readiness, and weak regulations related to the control of autonomous systems. This study recommends the establishment of a defense AI ethics council, revision of the defense legal framework to include intelligent technology, and the development of a collaborative roadmap across ministries. It is expected that the resulting policy will not only be adaptive to technological disruption, but also guarantee accountability and national sovereignty in the use of AI for strategic defense interests.